Multiple thermoluminescence glow peaks and afterglow suppression in CsI:Tl co-doped with Eu2+ or Yb2+. Issue 1 (March 2015) - Bartram, R H; Kappers, L A; Hamilton, D S; Brecher, C; Ovechkina, E E; Miller, S R; Nagarkar, V V
Abstract: CsI:Tl is a widely utilized scintillator material with many desirable properties but its applicability is limited by persistent afterglow. However, effective afterglow suppression has been achieved by co-doping with divalent lanthanides. The present report is concerned with observation of multiple thermoluminescence glow peaks in CsI:Tl, Eu and CsI:Tl, Yb, attributed to varying distributions of charge-compensating cation vacancies relative to divalent lanthanide co-dopants, and the subsequent modification of these distributions by repeated observations. It is observed that Yb 2+ provides a slightly shallower electron trap than Eu 2+, and that it can occupy a face-centered position by virtue of its relatively small ionic radius; the latter observation is confirmed by electrostatic calculations. It is also found that repeated observation of thermoluminescence in these materials has a modest adverse effect on afterglow suppression.